DESENVOLVIMENTO DE MÉTODOS VOLTAMÉTRICOS UTILIZANDO PLANEJAMENTO FATORIAL PARA DETERMINAÇÕES SIMULTÂNEAS DE ASSOCIAÇÕES FARMACÊUTICAS E COSMÉTICAS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The development and validation of analytical methods for quantification of two associations, antibiotics: sulfamethoxazole (SMX) and trimethoprim (TMP); and depigmenting agents: kojic acid (AK) and hydroquinone (HQ), using unmodified glassy carbon electrode (ECV) and square wave voltammetry (SWV) are described. For the first association, two well defined irreversible oxidation peaks were obtained at 0.96V (SMX) and 1.12V (TMP) in Britton–Robinson buffer (pH 6.0), characterized by diffusion and adsorptive processes, respectively. SWV parameters were optimized by means of 23 Full Factorial Design, and the best analytical signal, in terms of sensitivity and selectivity is obtained at a=30 mV, f=100 s-1 and ΔES=5mV. Under optimized conditions, SWV measurements showed excellent linear response, from 5.5x10-5 to 3.95x10-4 mol L-1 (R=0.9971) and 1.05x10-5 to 1.04x10-4 mol L-1 (R=0.9974) for SMX and TMP, respectively. The detection and quantification limits were found to be 8.52x10-6 mol L-1 and 2.84x10-5 mol L-1 for SMX; and 9.31x10-7 mol L-1 and 3.10x10-6 mol L-1 for TMP, respectively. The proposed method was successfully applied to the simultaneous determination of these antibiotics in commercial pharmaceutical formulations (tablets, oral suspension and injection), without any sample pretreatment. The obtained results are in good agreement with that obtained by the standard HPLC method at a 95% confidence level. For the second association, the redox peak potentials were completely separated in Mcllvaine buffer solution (pH 8.0), KA exhibits a well-defined irreversible oxidation peak at 0.72V and HQ a quasi-reversible redox peak at 0.08 V and -0.02 V, characterized by adsorptive and diffusional processes, respectively. Under SWV parameters optimized (a= 40 mV, f=40 s-1 and ΔES=1mV) by 23 Full Factorial Design, the calibration curves were obtained in the concentration ranges of 3.5×10-5 to 2.5×10-4 mol L-1 (R= 0.9996) for kojic acid and 1.5×10-5 to 1.6×10-4 mol L-1 (R= 0.9994) for hydroquinone. The detection and quantification limits were found to be 7.84x10-6 mol L-1 and 2.61x10-5 mol L-1 for KA; and 3.71x10-6 mol L-1 and 1.24x10-5 mol L-1 for HQ, respectively. The novel electroanalytical method was validated in terms of specificity, linearity, range, accuracy and precision (repeatability and intermediate precision) and successfully applied to the direct simultaneous determination of these bleaching agents in real samples.
Keywords: Ácido Kójico; Hidroquinona; Sulfametoxazol; Trimetoprima; carbono vítreo; voltametria de onda quadrada; planejamento fatorial de experimentos; formulações farmacêuticas; Kojic Acid; Hydroquinone; Sulfamethoxazole; Trimethoprim; glassy carbon electrode; square wave voltammetry; full factorial design; pharmaceutical formulations; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA